A Fast and Cost-Effective (FACE) Instrument Setting to Construct Focus-Extended Images - Audira, Gilbert; Hsu, Ting-Wei; Chen, Kelvin H.-C.; Huang, Jong-Chin; Lin, Ming-Der; Ger, Tzong-Rong; Hsiao, Chung-Der (Inventions (Basel), 2022)
Image stacking is a crucial method for micro or macro photography. It captures images at different focal planes and then merges them into a single, all-in-focus image with extended focus. This method has been extensively used for digital documentation by scientists working at museums or research institutions. However, the traditional image stacking method relies on expensive instruments to conduct precise image stacking using a computer-based stepper motor controller. In this study, we reported how to conduct image focus extensions with comparable quality to those done by a motorized stepper using a cost-effective instrument setting and an efficient manual stacking method. This method provides a shorter operation time and capability to capture images of living objects and high flexibility in obtaining the images of objects from cm to mm scale. However, it also has some limitations, including the inability to control aperture and exposure time, relatively short working distance at high magnification, requires additional steps to convert the video into images, and heavily relies on the user’s manual observation prior to a video recording. Nevertheless, the authors believe that the current method can be applied as an alternative method to conduct image stacking. The development of such an instrument and method offers a promising avenue for scientists to perform image stacking with greater flexibility and speed in macro photography.